Enhancing Self-Directed Learning in Medical Education Through Digital Tools - Nargis Haider, Aisha Zia Butt, Misbah Ul Hasan Ghani, Aliya Ishaque, Masooma Sajjad, Attia Sheikh (International Journal of Pharmacy Research & Technology (IJPRT), 2025)
Self-directed learning (SDL) is increasingly recognized as an essential component of competencybased medical education, fostering critical thinking, problem-solving, and lifelong learning. Therapid adoption of digital technologies has created unprecedented opportunities to enhance SDL in medical students by offering flexible